THE INFLUENCE OF WORKLOAD AND PERCEPTION OF ORGANIZATIONAL SUPPORT ON WORK PRODUCTIVITY OF EMPLOYEES IN THE OPERATIONS DEPARTMENT OF PT XYZ BANDUNG - Rizki Wira Utami; Khaerul Rizal Abdurahman (Universitas KH. Abdul Chalim Mojokerto, 2026)
Work productivity plays an important role in achieving company goals because it reflects the company's ability to manage resources effectively and efficiently. However, research findings at PT. XYZ Bandung indicate that work productivity is not optimal and has the potential to hinder the achievement of company goals. Productivity is influenced by several factors, such as workload and perceived organizational support. Based on data on targets and realizations for the CT7 engine work in 2020–2024, there was a decrease in targets and realizations in 2024 even though the aviation sector had stabilized, and delays in engine work still frequently occurred. This study aims to determine the influence of workload and perceived organizational support on work productivity among employees of the Operations Department of PT. XYZ Bandung, both partially and simultaneously. This study uses quantitative methods that include descriptive and associative data analysis, and the type of data used is primary data. Respondents totaling 60 employees of the operations department at PT. XYZ Bandung were given a questionnaire. Data analysis was conducted using multiple regression and data processing was conducted using SPSS version 26. The results of the study indicate that workload partially has a positive influence on employee work productivity, while perceived organizational support has no influence on employee work productivity, but simultaneously has an influence on employee work productivity. This means that the more appropriate the workload given by the company is to the potential and capacity of employees, the more work productivity will increase. Meanwhile, the lack of influence of perceived organizational support indicates that in carrying out their work, employees are more oriented towards fulfilling their duties and responsibilities to the company.